分裂逆向的人生与词风 ：以“纳兰性德”现象为探讨中心 = Contrast between personal life and creation style : focus on "Nalan Xingde" phenomenon - 张洁恩 Chong, Magdalene Kiat En (2019)
文学创作风格的形成各家有不同的说法，生平遭遇铸就作品风格是最为常见的风格形成模式，且诸多文人学者都为此模式提供许多例子与论述。但生平遭遇却并非唯一能够影响创作风格的因素，作者本人的性格或许方是最为核心的风格塑造条件。笔者在本文中，以“纳兰性德”现象为中心，探讨作者的性格对于作品风格的塑造。以纳兰性德的生平与其词风的比对，归纳出分类反差逆向风格文人所必须具备的条件。以两位不同朝代但与纳兰性德一样同属凄婉词人群的词人秦观与顾贞观为例，通过纵向与横向比较，分析纳兰性德与他们的不同之处，即人生过程与个人性格有着较大反差。此外，从另外两位不同时代的文人冯延巳与席慕容身上，找出与纳兰性德相似的共同点，即人生平顺但文风凄婉，人生旅程与作品风格呈现出一种分裂逆向的现象，分析其形成原因，探讨此类型文人可以称之为文学史上的“纳兰性德”现象。 The formation of literary creation style has various explanation. The experience of life is the most common effect of style formation. Even though many researchers and academics have provided examples and arguments for this formation style, authors’ life experience is not the only effect for the creation style. Authors’ personality and character should be the core factors in the creation style. This paper will explore the shaping capability of author’s personality and character to the creation style, by focusing “Nalan Xingde” phenomenon. In the first chapter, this paper will summarize the conditions for classified the literati as the contrast style by comparing the life and creation style with Nalan Xingde. Secondly, this paper compares Nalan Xingde and two literati from different dynasties but have exactly same style as Nalan Xingde, and the differences between them are life experience and personal character. In the third chapter, the paper will find out the similarities of Nalan Xingde with two literati in different eras, the smooth life and similar style, which are not corresponding. Explore the reason of this formation and find out whether this type of literati can be classified as a literary phenomenon which named as “Nalan Xingde”.